Hepatitis B virus reactivation and antiviral prophylaxis during lung cancer chemotherapy: A systematic review and meta-analysis. - Yu-Tuan Wu; Xin Li; Zi-Li Liu; Zhou Xu; Wei Dai; Ke Zhang; Jiu-Song Wu; Bilal Arshad; Kai-Nan Wu; Ling-Quan Kong (PLoS ONE, 2017)
Background Antiviral drugs have been recommended as prophylaxis for the reactivation of hepatitis B virus (HBV) infection in cancer patients undergoing chemotherapy. However, screening and antiviral prophylaxis for lung cancer remain controversial because of insufficient evidence. Purpose In this study, we investigate the absolute risk for HBV reactivation and the prophylactic effects of antiviral drugs in hepatitis B surface antigen (HBsAg)-positive lung cancer patients during chemotherapy. Methods We searched Pubmed, Embase, Cochrane, Web of Science and SinoMed from inception until 28 November 2016, and identified all potential relevant references with or without prophylactic use of antiviral therapy in HBsAg-positive lung cancer patients during chemotherapy. The primary outcome was the incidence of HBV reactivation, the secondary outcomes were the incidence of hepatitis, chemotherapy disruption and mortality. Results Eleven studies involving 794 patients were analyzed. The incidences of HBV reactivation in control group and antiviral prophylaxis group ranged from 0% to 38% (median, 21%, 95% CI: 0.17-0.25) and 0% to 7% (median, 4%, 95% CI: 0.02-0.06), respectively. Antiviral prophylaxis had significantly reduced the risk for HBV reactivation (RR, 0.22 [95% CI: 0.13-0.37], p< 0.0001), hepatitis (RR, 0.35 [95% CI: 0.22-0.56], p<0.0001) and chemotherapy disruption (RR: 0.29 [95% CI, 0.15-0.55], p<0.0002) compared to those without antiviral prophylaxis. There was no significant heterogeneity in the comparisons, and a fixed-model was used. Conclusion The risks of HBV reactivation and relevant complications are high in HBsAg-positive lung cancer patients receiving chemotherapy, and available evidences support HBV screening for antiviral prophylaxis before initiation of chemotherapy for lung cancer patients.